PENGARUH PEMBELAJARAN PAI BERBASIS BUDAYA TOLERANSI TERHADAP PERILAKU ANTI BULLYING DI SMPN 2 BALUNG - Moh. Nur Akbar Hafizul Ilmi; Hairul Huda; Dhian Wahana Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The phenomenon of bullying in junior high schools has become a serious issue that threatens the moral integrity and psychosocial well-being of students as a whole. This study was conducted as a response to this urgency by referring to the social dynamics occurring at SMP Negeri 2 Balung, where bullying cases had sharply increased during the COVID-19 pandemic period in 2020, but gradually declined after the school consistently implemented learning based on tolerance values. The theoretical foundation of this study is based on the concept of multicultural education proposed by James A. Banks (1989), which emphasizes that an inclusive education system is the main foundation for creating fair and harmonious social relations. This conceptual framework was operationalized through Islamic Religious Education (PAI) learning based on a culture of tolerance as the independent variable, while anti-bullying behavior was positioned as the dependent variable in this study.This study employed an associative quantitative approach using a Likert-scale questionnaire as the data collection instrument. The respondents consisted of 138 eighth-grade students selected through random sampling from a total population of 272 students. Data analysis was carried out through several stages, including validity, reliability, normality, linearity, simple linear regression, Pearson product-moment correlation, and coefficient of determination tests using SPSS software. The results of the data analysis revealed that tolerance culture-based Islamic Religious Education learning had a positive and significant influence on the development of anti-bullying behavior among students. The coefficient of determination value of 0.334 indicates that tolerance culture-based PAI learning contributed 33.4% to anti-bullying behavior variables.